ETHNOZOOLOGY- FAUNAL DIVERSITY IN FOLKLORES OF SHEKHAWATI, RAJASTHAN - Soni, Shikha; Chandra, Subhash; Sharma, Anima (International Journal of Research -GRANTHAALAYAH, 2025)
Background- The body of knowledge, practice, and belief regarding the relationships between living things, including humans, and their environment that has been passed down through the generations via cultural transmission and evolved through adaptive processes is known as traditional ecological knowledge. It is also considered to be a part of cultural folklore. Traditional ecological knowledge and folklore are rich sources of knowledge about the natural world. As a result, the goal of the current study is to learn more about the animals’ place in folklore and sociocultural practices in Shekhawati region, Rajasthan. Method- The ethnozoological data about folk lore were acquired through an emic method, utilizing several tools such as semi-structured interviews, participatory rural appraisal, key informant interviews, and focus group discussions. Result- The study found 381 animals related folk lore. In which class Mammalia related folk lore are highest in number that is 276 (72.44%) followed by class aves 51 (13.38%), followed by phylum Arthropoda 28 (7.34%), followed by class Reptilia 23 (6.03%), and then Annelida 1 (0.26%), Mollusca 1 (0.26%) and Amphibia 1 (0.26%). Conclusion- Rajasthan’s ethnic people closely relate to the environment, using plants and animals for transportation, food, medicine, weather forecasting, fortune telling, and cultural and religious purposes. Documenting this ethnozoological knowledge is crucial to prevent its loss.